2009
DOI: 10.1097/meg.0b013e32831b4698
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and treatment of hyperlipidemia in patients with chronic hepatitis C infection

Abstract: A high prevalence of hyperlipidemia in patients infected with HCV is observed. Prevalence is highest among those who are positive for viral RNA. About half the patients with hyperlipidemia were eligible for treatment with drugs to lower it. Treatment of hyperlipidemia with medication though surprisingly common could improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The main function of lipoproteins is transporting lipids throughout the body. Our report also showed hyperlipidaemia was associated with anti‐HCV seropositivity in persons with severe haemophilia, which was consistent with previous studies indicating a high prevalence (70%) of hyperlipidaemia in general population infected with HCV 9 …”
Section: Total Number (N = 245) Era a < 1990 Era B 1990 ‐ 2000 Era C ≧ 2000 P Value N = 122 % N = 61 % N = 62 %supporting
confidence: 93%
See 1 more Smart Citation
“…The main function of lipoproteins is transporting lipids throughout the body. Our report also showed hyperlipidaemia was associated with anti‐HCV seropositivity in persons with severe haemophilia, which was consistent with previous studies indicating a high prevalence (70%) of hyperlipidaemia in general population infected with HCV 9 …”
Section: Total Number (N = 245) Era a < 1990 Era B 1990 ‐ 2000 Era C ≧ 2000 P Value N = 122 % N = 61 % N = 62 %supporting
confidence: 93%
“…Our report also showed hyperlipidaemia was associated with anti-HCV seropositivity in persons with severe haemophilia, which was consistent with previous studies indicating a high prevalence (70%) of hyperlipidaemia in general population infected with HCV. 9 Current therapeutic approaches have prolonged the life expectancies of PWH. Consequently, age-related comorbidities are an emerging issue as the population of elder continues to rise, resulting in an increased demand for comprehensive haemophilia care.…”
mentioning
confidence: 99%
“…[1,2] Accumulative evidence suggested that HCV infection could exist in the heart, pancreas, kidneys, ovaries, [35] and even in placenta. [6,7] There is a growing body of data concerning the role of HCV in extrahepatic manifestations, including cardiovascular diseases, [8,9] immunological disorders, [10] and neurodegenerative diseases. [11,12] Placenta is a crucial organ during pregnancy for intrauterine fetal growth.…”
Section: Introductionmentioning
confidence: 99%
“…9 Previous studies also noted that progression of CHCV infection is influenced by clinical manifestations of metabolic syndrome. 10 We did this study with an aim to find out association of lipid profile and body mass index (BMI) profile among cases having CHCV infection. The results of Body Mass Index and Lipid Profile Pak Armed Forces Med J 2021; 71 (6): 1986 this study might prove useful giving us clue about monitoring and potential management of lipid profile and BMI when cases of CHCV infection are confronted.…”
Section: Introductionmentioning
confidence: 99%